2021
DOI: 10.1021/acs.macromol.0c02052
|View full text |Cite
|
Sign up to set email alerts
|

Ion Diffusion in Chemically Amplified Resists

Abstract: The acid-catalyzed deprotection of glassy polymer resins is an important process in semiconductor lithography. Studies have shown that the reaction kinetics in these materials is controlled by slow diffusion of the acid−anion catalyst, but trends deviate from models of a first-order reaction coupled to a composition-invariant Fickian diffusivity. We present a concerted experimental and computational effort to examine catalyst diffusion in a model resin of poly(4-hydroxystyrene-co-tert-butyl acrylate-co-styrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(63 citation statements)
references
References 85 publications
3
59
0
Order By: Relevance
“…There are characterization needs in polymer science where ToF‐SIMS could be very valuable. As an example, studies have shown that ToF‐SIMS depth profiling can probe penetrant diffusion in glassy polymers 102 as well as interdiffusion of polymers and small molecules 152 . The key advantage of using ToF‐SIMS for diffusion studies is the intrinsic chemical contrast, which is particularly important when probing materials with complex chemical motifs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are characterization needs in polymer science where ToF‐SIMS could be very valuable. As an example, studies have shown that ToF‐SIMS depth profiling can probe penetrant diffusion in glassy polymers 102 as well as interdiffusion of polymers and small molecules 152 . The key advantage of using ToF‐SIMS for diffusion studies is the intrinsic chemical contrast, which is particularly important when probing materials with complex chemical motifs.…”
Section: Discussionmentioning
confidence: 99%
“…Depth profiling can be used to probe diffusion of a small molecule penetrant in a thin polymer film. As an example, Bottoms et al examined diffusion of sodium triflate in a polymeric photoresist, 102 where sodium triflate was employed as an inert analogue of a common catalyst (acid triflate). They prepared bilayers with a base “feeder layer” containing sodium triflate and a top “diffusion layer” that initially contained no ions.…”
Section: Analysis Of Polymer Films and Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion of small penetrants in inert polymer melts and glasses has been a subject of numerous studies, with atomistic and molecular simulations expanding our fundamental understanding of these processes. It is now well established that a subdiffusive regime can be present for displacements over length scales of a few nanometers. This was attributed to (1) the movement of penetrants being controlled by the size, shape, and connectivity of an infrequently present transient volume between polymer chains, as well as the size of the penetrant, , and (2) the strength of enthalpic interactions between the penetrant and polymer, impacting short-range penetrant dynamics. , With recent advancements in modeling and computational power, molecular simulations have been increasingly employed to study ion diffusion in polymers, in the presence of strong ionic interactions. In addition, recent molecular simulations have shown that intermolecular interactions are an important consideration for catalyst diffusion in inert CAR systems. , All of these prior studies provide a solid fundamental framework for molecular diffusion in polymeric systems without reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature has shown that catalyst diffusion during reaction has an apparent time dependence . Others have hypothesized that this time dependence is associated with changes in polymer composition, ,, catalyst–polymer, or catalyst–catalyst interactions, or a short-lived increase in free volume from the generation and (assumed) fast escape of volatile reaction byproducts. In our most recent study, we examined the first two hypotheses using a model CAR system based on a terpolymer resin and inert catalyst analogue (ion pair) with atomistic simulations and Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS) experiments. The findings showed that in the absence of reaction, ion pair diffusion is polymer composition and catalyst concentration invariant.…”
Section: Introductionmentioning
confidence: 99%